Somatic Copy Number Abnormalities and Mutations in PI3K/AKT/mTOR Pathway Have Prognostic Significance for Overall Survival in Platinum Treated Locally Advanced or Metastatic Urothelial Tumors - Bellmunt, Joaquim (PLoS One, 2015)
BACKGROUND: An integrative analysis was conducted to identify genomic alterations at a pathway level that could predict overall survival (OS) in patients with advanced urothelial carcinoma (UC) treated with platinum-based chemotherapy. PATIENTS AND METHODS: DNA and RNA were extracted from 103 formalin-fixed paraffin embedded (FFPE) invasive high-grade UC samples and were screened for mutations, copy number variation (CNV) and gene expression analysis. Clinical data were available from 85 cases. Mutations were analyzed by mass-spectrometry based on genotyping platform (Oncomap 3) and genomic imbalances were detected by comparative genomic hybridization (CGH) analysis. Regions with threshold of log(2) ratio ≥0.4, or ≤0.6 were defined as either having copy number gain or loss and significantly recurrent CNV across the set of samples were determined using a GISTIC analysis. Expression analysis on selected relevant UC genes was conducted using Nanostring. To define the co-occurrence pattern of mutations and CNV, we grouped genomic events into 5 core signal transduction pathways: 1) TP53 pathway, 2) RTK/RAS/RAF pathway, 3) PI3K/AKT/mTOR pathway, 4) WNT/CTNNB1, 5) RB1 pathway. Cox regression was used to assess pathways abnormalities with survival outcomes. RESULTS: 35 samples (41%) harbored mutations on at least one gene: TP53 (16%), PIK3CA (9%), FGFR3 (2%), HRAS/KRAS (5%), and CTNNB1 (1%). 66% of patients had some sort of CNV. PIK3CA/AKT/mTOR pathway alteration (mutations+CNV) had the greatest impact on OS (p=0.055). At a gene level, overexpression of CTNNB1 (p=0.0008) and PIK3CA (p=0.02) were associated with shorter OS. Mutational status on PIK3CA was not associated with survival. Among other individually found genomic alterations, TP53 mutations (p=0.07), mTOR gain (p=0.07) and PTEN overexpression (p=0.08) have a marginally significant negative impact on OS. CONCLUSIONS: Our study suggests that targeted therapies focusing on the PIK3CA/AKT/mTOR pathway genomic alterations can generate the greatest impact in the overall patient population of high-grade advanced UC.